2016
DOI: 10.3389/fmicb.2016.00932
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Cellulose Hydrolysis Dominated by a Multi-Modular Processive Endoglucanase from Clostridium cellulosi

Abstract: Recalcitrance of biomass feedstock remains a challenge for microbial conversion of lignocellulose into biofuel and biochemicals. Clostridium cellulosi, one thermophilic bacterial strain dominated in compost, could hydrolyze lignocellulose at elevated temperature by secreting more than 38 glycoside hydrolases belong to 15 different families. Though one multi-modular endoglucanase CcCel9A has been identified from C. cellulosi CS-4-4, mechanism of synergistic degradation of cellulose by various cellulases from st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 25 publications
0
18
0
1
Order By: Relevance
“…The samples were eluted at the speed of 1 ml/min via the use of an eluent consisting of 200 mM NaOH. In order to assess the synergy of each mixture, the degree of synergy (DOS) (23,39) was calculated using the following formula: DOS ϭ (total sugars released from enzyme mixture)/(total sugars released from incubation with individual enzymes). 1 H-NMR analysis of products.…”
Section: Methodsmentioning
confidence: 99%
“…The samples were eluted at the speed of 1 ml/min via the use of an eluent consisting of 200 mM NaOH. In order to assess the synergy of each mixture, the degree of synergy (DOS) (23,39) was calculated using the following formula: DOS ϭ (total sugars released from enzyme mixture)/(total sugars released from incubation with individual enzymes). 1 H-NMR analysis of products.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Oliva-Taravilla et al (2014) reported that the relative glucose recovery in presence of laccase with cellulosic substrate (Sigmacell and steam exploded wheat straw) was almost 10% lower than in the absence of laccase. Yang et al (2016) reported that the ratios and cooperation of cellulases are crucial in the hydrolysis and the efficiency could be further improved after adding accessory enzymes such as oxidoreductases, expansions, for which the bacterial enzyme pool is so abundant to excavate in the future (Agrawal et al, 2015d).…”
Section: Effect Of Supplementing Celluclast With Accessory Enzymesmentioning
confidence: 99%
“…In particular, the hydrolysis of complex polymers into smaller molecular weight molecules (which can be then metabolized into useful byproducts by other community members) is often a limiting step in bioconversion (Minty et al 2013;Kim et al 2014;Yang et al 2016) . As a proof of concept, we set out to apply artificial selection to find a community with an enhanced ability to hydrolyze starch.…”
Section: Resultsmentioning
confidence: 99%